Regional Economic Stability: Principal Pre-Requisite for Peace and Security. - Monnoo, Kamal (2010)
The paper concentrates on regional economic stability in terms of principal pre-requisite for peace and prosperity in the South Asian region. Arguments are put forward for the application of Krugman‘s model of regional cooperation in South Asia as region. The paper brings out that the focus on neighbourhood/proximity co-operation yields new yet tangible kinds of benefits and strengths through positive spillover effects which can be used for poverty alleviation in the region as a whole. Unhealthy rivalry, mistrust and animosity between India and Pakistan is regretted and cooperation among them on the pattern of formation of European Union is plead. In this endeavour active involvement of Pakistani and Indian people is highly recommended.